Interactive Audio Augmented Reality in Participatory Performance - Nagele, Anna N.; Bauer, Valentin; Healey, Patrick G. T.; Reiss, Joshua D.; Cooke, Henry; Cowlishaw, Tim; Baume, Chris; Pike, Chris (Frontiers in Virtual Reality, 2021)
Interactive Audio Augmented Reality (AAR) facilitates collaborative storytelling and human interaction in participatory performance. Spatial audio enhances the auditory environment and supports real-time control of media content and the experience. Nevertheless, AAR applied to interactive performance practices remains under-explored. This study examines how audio human-computer interaction can prompt and support actions, and how AAR can contribute to developing new kinds of interactions in participatory performance. This study investigates an AAR participatory performance based on the theatre and performance practice by theatre maker Augusto Boal. It draws from aspects of multi-player audio-only games and interactive storytelling. A user experience study of the performance shows that people are engaged with interactive content and interact and navigate within the spatial audio content using their whole body. Asymmetric audio cues, playing distinctive content for each participant, prompt verbal and non-verbal communication. The performative aspect was well-received and participants took on roles and responsibilities within their group during the experience.